Retinoscopes: Past and present - Musa, Mutali; Enaholo, Ehimare; Bale, Babatunde Ismail; Salati, Carlo; Spadea, Leopoldo; Zeppieri, Marco (World journal of methodology, 2024)
Retinoscopy is arguably the most important method in the eye clinic for diagnosing and managing refractive errors. Advantages of retinoscopy include its non-invasive nature, ability to assess patients of all ages, and usefulness in patients with limited cooperation or communication skills. To discuss the history of retinoscopes and examine current literature on the subject. A search was conducted on the PubMed and with the reference citation analysis (https://www.referencecitationanalysis.com) database using the term "Retinoscopy," with a range restricted to the last 10 years (2013-2023). The search string algorithm was: "Retinoscopy" (MeSH Terms) OR "Retinoscopy" (All Fields) OR "Retinoscopes" (All Fields) AND [(All Fields) AND 2013: 2023 (pdat)]. This systematic review included a total of 286 records. Publications reviewed iterations of the retinoscope into autorefractors, infrared photo retinoscope, television retinoscopy, and the Wifi enabled digital retinoscope. The retinoscope has evolved significantly since its discovery, with a significant improvement in its diagnostic capabilities. While it has advantages such as non-invasiveness and broad applicability, limitations exist, and the need for skilled interpretation remains. With ongoing research, including the integration of artificial intelligence, retinoscopy is expected to continue advancing and playing a vital role in eye care.